Pneumococcal vaccination at disease onset: new strategies of protection against pneumococcal infection in children with idiopathic nephrotic syndrome. Issue 2 (April 2009) - Ulinski, Tim
Children with idiopathic nephrotic syndrome are at risk of potentially severe pneumococcal infections, such as pneumonia, meningitis and peritonitis. This susceptibility is due to losses of immunoglobulin and complement system components. Strategies to reduce the risk of pneumococcal infections include antibiotic prophylaxis (abandoned as a result of an increased risk to select resistant strains) and antipneumococcal vaccination. Traditionally, vaccination was performed when the patient was in remission and on low-dose steroids. A recent study has demonstrated that nephrotic children on high-dose glucocorticoid therapy respond to a pneumococcal polysaccharide vaccine. The major advantage of this strategy is that patients who relapse during the tapering of steroids already have increased anti-pneumococcal antibodies at the time of relapse. Patients with steroid-dependent or -resistant forms of the nephrotic syndrome acquire high antibody levels even if early relapses delay the tapering of steroids or if immunosuppressive agents are introduced. The fear of vaccine-induced relapses creates hesitation concerning vaccination of children with idiopathic nephrotic syndrome in remission. 23-valent pneumoccal vaccine at disease onset may therefore increase the number of pneumococcal vaccinations in children with the nephrotic syndrome. Vaccination with a 23-valent pneumoccal vaccine at disease onset while the patient is proteinuric and on high-dose steroids is a safe strategy with a high antibody response.